Did the UK's public health shielding policy protect the clinically extremely vulnerable during the COVID-19 pandemic in Wales? Results of EVITE Immunity, a linked data retrospective study. (May 2023) - Snooks, H.; Watkins, A.; Lyons, J.; Akbari, A.; Bailey, R.; Bethell, L.; Carson-Stevens, A.; Edwards, A.; Emery, H.; Evans, B.A.; Jolles, S.; John, A.; et al.
Abstract: Introduction: The UK shielding policy intended to protect people at the highest risk of harm from COVID-19 infection. We aimed to describe intervention effects in Wales at 1 year. Methods: Retrospective comparison of linked demographic and clinical data for cohorts comprising people identified for shielding from 23 March to 21 May 2020; and the rest of the population. Health records were extracted with event dates between 23 March 2020 and 22 March 2021 for the comparator cohort and from the date of inclusion until 1 year later for the shielded cohort. Results: The shielded cohort included 117, 415 people, with 3, 086, 385 in the comparator cohort. The largest clinical categories in the shielded cohort were severe respiratory condition (35.5%), immunosuppressive therapy (25.9%) and cancer (18.6%). People in the shielded cohort were more likely to be female, aged ≥50 years, living in relatively deprived areas, care home residents and frail. The proportion of people tested for COVID-19 was higher in the shielded cohort (odds ratio [OR] 1.616; 95% confidence interval [CI] 1.597–1.637), with lower positivity rate incident rate ratios 0.716 (95% CI 0.697–0.736). The known infection rate was higher in the shielded cohort (5.9% vs 5.7%). People in the shielded cohort were more likely to die (OR 3.683; 95% CI: 3.583–3.786), have a critical care admission (OR 3.339; 95% CI: 3.111–3.583), hospital emergency admission (OR 2.883; 95% CI: 2.837–2.930), emergency department attendance (OR 1.893; 95% CI: 1.867–1.919) and common mental disorder (OR 1.762; 95% CI: 1.735–1.789). Conclusion: Deaths and healthcare utilisation were higher amongst shielded people than the general population, as would be expected in the sicker population. Differences in testing rates, deprivation and pre-existing health are potential confounders; however, lack of clear impact on infection rates raises questions about the success of shielding and indicates that further research is required to fully evaluate this national policy intervention.